SUGRĮŽIMAS PRIE HOULDENO: FILOSOFINĖ PERSONAŽO PRIGIMTIES STUDIJA. - Pučiliauskaitė, Saulenė (Problems / Problemos, 2010)
This article is our attempt to investigate, as independently as possible, some philosophical problems concerning literature. First, it is the relationship between the writer and the literary character; second, it is the reality of a literary character, and third -- it is the relationship between literature and reality. During our discussion, we come across its possible interpretation in the postmodern context, namely the concept of simulacrum, and leave it behind. And even though our investigation does no exhaust all the field of study, as an attempt to draw its shape it can be applied to solve some internal questions concerning man's relation to literature.